Combined Effect of Textile Waste and Meta Kaolin on the Properties of Polymer Concrete in Pavements (International Journal of Innovative Research in Engineering & Management, 2023)
The current era sees a significant impact on  society, especially individuals concerned with sustainability  and environmental well-being due to the utilization of  unconventional materials in construction. The present  scientific study concentrates on investigating how Textile  waste combined with Meta kaolin affects mechanical  attributes of polymer concrete. The enhancement of cement  concrete pavement with polymer modification has recently  captured the attention of those researching new road  materials. Indoor testing methods that explore compressive  strength, flexural strength, have been employed to  investigate this innovative approach. These varying  properties were measured using different levels of polymer  content in a comprehensive study aimed at improving joint damage and reducing cracks in cement concrete pavements.  The study analysed the actions of polymer concrete  combined with discarded textiles trimmings. Each trial  incorporated reused chopped fibers, representing 1% and  2% of total weight respectively.
Keywords: Polymer; Meta kaolin; Concrete; Pavement; Strength